France in the European Union - Zečević, Slobodan (Napredak, 2025)
The French state is the founder and the foundation on which today’s European Union lies. The European Union has survived the exit of Great Britain and it might also survive the exit of some other of its member-states, but it is almost certain that it could not exist without France in its ranks. The French constitutional concept and political system are specific in comparison to other EU member-states because of their Gaullist heritage – the intention of preserving national autonomy in the fields of foreign politics, defence, energy, healthcare, culture and education. However, Frenchmen have understood for a long time that they cannot enter a fair match with the powers such as the United States of America, China, Russia, as well as India in the near future. The autonomous European Union under French influence is the only entity that would have resources for something like that, and it is exactly the program and political idea France is trying to realize, currently with no success.